Climate dashboard prototype: System setup and development documentation - Ogero, Derrick; Basel, Ashleigh; Chepngetich, Brenda; Craparo, Alessandro (2025)
This documentation outlines the initial setup and development steps for a prototype climate dashboard backend and frontend. The system leverages various tools like Docker, PostGIS, GeoServer, and Django for managing and serving climate hazard data. This dashboard allows users to interact with geospatial data layers and view climate risk visualizations.